Policy Responses to Covid-19 In Ireland: Supporting Individuals, Communities, Businesses, and the Economy - Hamill, Sarah; Walsh, Rachael; Bell, Mark; Fennelly, David; Ryan, Desmond; Seretakis, Alexandros; Clarke, Blanaid; Ahern, Deirdre (Trinity College Dublin, 2020)
The aim of the Observatory’s policy report series is to contribute actively to public debate and to shape public policy and law reform through analysing and evaluating Ireland’s response to COVID-19. Crucially, unlike the last recession arising out of the global financial crisis of 2008-2009, the current recession is caused by an unprecedented health crisis and not economic mismanagement. As matters stand, a vaccine is not available that would readily permit live to resume as before. This affects the policy levers that can be used to address living with COVID-19. Ireland, like most of the world, has responded to the COVID-19 pandemic with an unprecedented series of restrictions on everyday life, designed to stem the spread of the virus in the interests of the common good. These restrictions have, in turn, imposed significant costs on individuals, families, and businesses. There have been specific State measures taken on social welfare, housing, business protection, disability and employment. Major issues of public policy arise in relation to the implications of COVID-19 responses from the State. In this Report, the contributors outline some of those costs and chart the various measures taken by the State in an attempt, insofar as is possible, to preserve normal individual, family, and business life through the pandemic. They also identify a number of issues that require attention and make recommendations for reform—focused both on further stages of pandemic and lessons learned for resuming normal life after the pandemic. Looking outside of Ireland, the European Commission’s establishment of the Generation EU fund provides hope to Ireland and other Member States where the financial prognosis of coping with COVID-19 can only get worse before it gets better and a vaccine against COVID-19 is rolled out. Notably, if Ireland wants to access grants and loans from the fund it will have to have a credible plan not just for economic recovery, but also for enabling the sustainability, circular economy agenda of the Green Deal and digital transition. This may have important beneficial public policy ripple effects for the future of our country. The Report begins with an examination of how individuals have been protected in their homes and in their workplaces, before exploring the social protection supports for those who have lost their jobs. We then move to the supports for businesses, with a focus on the opportunities and limits of insurance for business disruption, alongside measures that enable the continued functioning of corporate governance mechanisms. Conditional governmental support to companies can be consistent with influencing them to broaden their corporate purpose beyond profit maximisation and considering broader stakeholder interests. One can see elements of this in the requirement that companies accessing the COVID-19 Wage Subsidy Scheme retain their employees on the payroll. The Report then analyses how the international financial markets have enabled the continued borrowing of funds by the State to support the State’s response. While these responses are, at one level, a matter for public policy, they can also be seen as an implementation of the socioeconomic rights of citizens. The Report therefore concludes with an analysis of the State’s response through a human rights lens. Although this Report does not purport to be a legal guide to relevant measures in force, it bears mentioning that the rules, regulations and restrictions associated with the presence of COVID-19 in Ireland in 2020 have adapted and evolved, often rapidly. The chapters in this Report were submitted by the authors for review and copy-editing at the beginning of October 2020, before the announcement of the national Level 5 lockdown applicable from 21 October 2020. We are very thankful to our colleagues for providing their expertise and insights in the chapters of this Report and to the Observatory in order to contribute to national public debate on COVID-19.
PUBLISHED
Contributes to national public debate on COVID-19 and policy-making by the State.
Keywords: Identities in Transformation; Inclusive Society; Making Ireland; Commercial Law; Corporate Governance; EMPLOYMENT LAW; Insurance law; Property Law; Community; Employment; Environment and housing; Globalization; Justice and safeguarding; Legislation; Policy; Social exclusion; Social participation; Social services, interventions and supports